2014
DOI: 10.1071/en14069
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of arsenolipids by the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Environmental context. Arsenic biotransformation processes play a key role in the cycling of arsenic in aquatic systems. We show that a freshwater cyanobacterium can convert inorganic arsenic into arsenolipids, and the conversion efficiency depends on the arsenic concentration. The role of these novel arsenic compounds remains to be elucidated.Abstract. Although methylated arsenic and arsenosugars have been verified in various freshwater organisms, lipidsoluble arsenic compounds have not been identified. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…In the past few years, the investigation of As-containing lipids (arsenolipids) and their possible role in the transformation and detoxification of As have gained interest. However, the structures of arsenolipids and derivatives in microalgae have been consistently overlooked while some of them have been identified (Dembitsky and Levitsky 2004;García-Salgado et al 2012b;Xue et al 2014). Moreover, identity and toxicity of these compounds are largely unknown due to lower levels of the lipid-soluble arsenic species in the marine environment, as well as difficulties associated with isolation and analysis of these compounds compared to water-soluble arsenic species (Dembitsky and Levitsky 2004;Duncan et al 2013aDuncan et al , b, 2015.…”
Section: Formation Of Arsenolipidsmentioning
confidence: 94%
See 3 more Smart Citations
“…In the past few years, the investigation of As-containing lipids (arsenolipids) and their possible role in the transformation and detoxification of As have gained interest. However, the structures of arsenolipids and derivatives in microalgae have been consistently overlooked while some of them have been identified (Dembitsky and Levitsky 2004;García-Salgado et al 2012b;Xue et al 2014). Moreover, identity and toxicity of these compounds are largely unknown due to lower levels of the lipid-soluble arsenic species in the marine environment, as well as difficulties associated with isolation and analysis of these compounds compared to water-soluble arsenic species (Dembitsky and Levitsky 2004;Duncan et al 2013aDuncan et al , b, 2015.…”
Section: Formation Of Arsenolipidsmentioning
confidence: 94%
“…), As(V) is absorbed into cells via phosphate transporters, while As(III) moves across plasma membrane via aquaglyceroporins (AQP) and hexose permeases (Cullen et al 1994;Levy et al 2005;Zhang et al 2014). The chemical similarity between PO 4 3-and AsO 4 3-suggests that these ions may show competitive behavior with regard to the phosphate uptake system (Andreae and Klumpp 1979;Johnson 1971;Xue et al 2014).…”
Section: Arsenic Uptake Into Algal Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“…Laboratory studies have shown that a variety of aquatic microalgae and bacteria species are capable of oxidizing As(III) to As(V) [35][36][37], reducing As(V) to As(III) [38,39], biomethylating As [38,40], or synthesizing complex arsenosugars or arsenolipids [35,41,42]. Laboratory studies have shown that a variety of aquatic microalgae and bacteria species are capable of oxidizing As(III) to As(V) [35][36][37], reducing As(V) to As(III) [38,39], biomethylating As [38,40], or synthesizing complex arsenosugars or arsenolipids [35,41,42].…”
Section: Introductionmentioning
confidence: 99%